Perception of corporate sustainability based on practices disclosed by the governance of state-owned companies (Revista Brasileira de Contabilidade e Gestão, 2023)
Objective: To investigate the perception of corporate sustainability based on practices disclosed by the governance of federal state-owned companies directly controlled by the Federal Government. Methods: This is an exploratory research, with a qualitative approach and analysis of corporate reports. The content analysis was carried out by surveying the compliance between the management reports of the state-owned companies and the GlobalReporting Initiative framework, by compliance with the economic, environmental, and social guidelines recommended by the regulatory body. Results: Corporate sustainability is perceived as the enforcement of cost reduction standards and practices by the governance. The governance of public companies and mixed-capital companies did not present an adequate perception of corporate sustainability as voluntary practices, as they only complied with the requirements resulting from possible inspections. For the governance of state-owned companies, presenting that the guidelines of the economic, environmental, and social pillarshave been complied with was a way of presenting themselves as more efficient. Environmental guidelines were the least complied with, despite the fact that many of the state-owned companies carried out the rational use of water, efficient energy consumption, waste management, and solidary selective waste collection. Contributions: The governances of state-owned companies were not socially responsible as well, despite the fact that theirsocial indices had better performance than their environmental ones. State-owned companiessummarized the social pillar as for providing training for their employees, and disclosed the compliance with recommended guidelines in the economic, environmental, and social pillars as responses to isomorphism and as a tool of legitimacy.
Keywords: corporate sustainability; governance; state-owned companies